Analisis Pengaruh Penerapan Sistem Informasi Akuntansi terhadap Efektivitas Pelayanan Nasabah pada Bank BRI - Ketrina Nabila; Arisky Andrinaldo; Sakina Wahid; Dani Milawati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Bank BRI, as one of the largest banks in Indonesia, is required to provide fast, accurate, and reliable services to its customers. To achieve this goal, the implementation of an Accounting Information System (AIS) plays a crucial role in supporting operational processes, particularly in transaction processing, financial information reporting, and enhancing service quality. This study aims to analyze the influence of AIS implementation on the effectiveness of customer service at Bank BRI. This research employs a descriptive quantitative method, as it describes the actual conditions related to service effectiveness and the use of AIS within the bank. Data were collected through questionnaires, observations, and documentation of customer service activities. The results show that the implementation of AIS at Bank BRI is adequate and has been carried out according to the essential elements of an effective information system. AIS has a positive impact on customer service effectiveness, as reflected in improved transaction speed, accuracy of information, reduced recording errors, and increased customer satisfaction. However, several limitations remain, such as variations in employee competencies and occasional technical disruptions. Overall, the implementation of AIS significantly influences and enhances the effectiveness of customer service at Bank BRI.